2006
DOI: 10.1007/bf03022836
|View full text |Cite
|
Sign up to set email alerts
|

Audit of factor VIIa for bleeding resistant to conventional therapy following complex cardiac surgery

Abstract: Purpose:There are an increasing number of anecdotal reports and trials of recombinant activated factor VII (rFVIIa) for bleeding during surgery. The reports of rFVIIa during cardiac surgery are limited. We report our experience using rFVIIa, in the operating room; to treat bleeding that prevented chest closure, despite appropriate conventional treatment, following complex cardiac surgery.Methods: Retrospective chart review, at an Australian University hospital and associated private hospital, of cardiac surger… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 27 publications
(48 reference statements)
0
31
1
Order By: Relevance
“…11 In cardiac surgery, mortality and complication rates of patients who have failed to respond to standard transfusion therapy and then received rFVIIa are in range of 19% to 40%. 10,14,24,25 The lack of control patients in most of these case series makes it difficult to determine whether the reported adverse events are related to the administration of rFVIIa or the critical unstable condition of patients when they received rFVIIa. When rFVIIa was used on a compassionate basis to reduce uncontrolled bleeding in 51 patients after cardiac surgery, propensity matching techniques to adjust for baseline risks demonstrated that the rates of cSAEs were equivalent.…”
Section: Safety Of Rfviiamentioning
confidence: 99%
See 2 more Smart Citations
“…11 In cardiac surgery, mortality and complication rates of patients who have failed to respond to standard transfusion therapy and then received rFVIIa are in range of 19% to 40%. 10,14,24,25 The lack of control patients in most of these case series makes it difficult to determine whether the reported adverse events are related to the administration of rFVIIa or the critical unstable condition of patients when they received rFVIIa. When rFVIIa was used on a compassionate basis to reduce uncontrolled bleeding in 51 patients after cardiac surgery, propensity matching techniques to adjust for baseline risks demonstrated that the rates of cSAEs were equivalent.…”
Section: Safety Of Rfviiamentioning
confidence: 99%
“…The committee's advice was based on the data within the expanding cardiac literature in which doses of rFVIIa were in the range of 60 g/kg. 6,9,10,15 Patients were randomized through an interactive voice response system and were always assigned to the lowest available randomization number. After randomization, freeze-dried powdered (4.8 mg) rFVIIa or placebo was reconstituted with 8.5 mL sterile water and administered as a bolus injection.…”
Section: Randomization Study Monitoring and Maskingmentioning
confidence: 99%
See 1 more Smart Citation
“…The evidence on rFVIIa in refractory bleeding associated with cardiac surgery is currently limited to observational studies consisting of case reports (not referenced), case series, [27][28][29][30][31][32][33][34][35][36][37][38][39][40] and case-control studies. [41][42][43][44][45] These observational studies have important limitations such as reporting bias in favour of the intervention and inability to fully adjust for the effects of confounding variables.…”
Section: Rationalementioning
confidence: 99%
“…However, these methods gave only indirect evidence of the graft patency; a postoperative intracardiac catheterization was not performed. The usefulness of rFVIIa in inherited or acquired bleeding disorders had been published on cardiac surgical patients [5][6][7][8]. Al-Douri et al [9] evaluated the role of rFVIIa in 5 patients (1 child, aged 2.5 years, and 4 adults) who underwent different surgical procedures.…”
Section: Discussionmentioning
confidence: 99%